The affordability of "affordable" housing in England: conditionality and exclusion in a context of welfare reform. Issue 7 (8th August 2020) - Preece, Jenny; Hickman, Paul; Pattison, Ben
Abstract: Contemporary debates around affordability have largely focused on homeownership and private renting. This article considers the affordable social rented sector in England, in which reforms to social welfare assistance, reduced security of tenure, and a shift towards mid-market rents, are changing access to 'affordable' housing for those on the lowest incomes. Drawing on in-depth interviews with housing associations and stakeholders, the article highlights the increasing use of affordability assessments for prospective tenants. These assessments interact with mid-market rental products to increase the potential for exclusion from affordable housing on the grounds of ability to pay. This conditionality is applied not only at the point of tenancy access, but also at renewal of fixed-term tenancies. The research highlights that the combination of welfare and housing policies, in the context of a financialising housing association sector, has the potential to erode access to social housing for those who are perceived as a financial risk, reshaping the focus of social housing.